Perbandingan Metode Pemulihan: Rendaman Kaki di Es vs. Istirahat Aktif Pasca Latihan Lari 12 Menit Mahasiswa PKO UPRI - Muhammad Arkanul Arba'; Wahyu Rahmatullah (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to compare the effectiveness of ice water immersion versus active recovery methods on recovery after 12-minute running exercise in sports coaching education students. This research used a quasi-experimental design with a sample of 30 students divided into two groups: ice water immersion group (n=15) and active recovery group (n=15). Recovery parameters measured included heart rate recovery, blood lactate levels, and perceived exertion scale. Data were analyzed using independent t-test and paired t-test with significance level p<0.05. The results showed that both recovery methods were effective in reducing heart rate and blood lactate levels post-exercise. However, the ice water immersion group showed significantly faster heart rate recovery (p=0.032) and lower lactate clearance time (p=0.028) compared to the active recovery group. The active recovery group showed better subjective recovery perception (p=0.041). This study concludes that ice water immersion is more effective for physiological recovery, while active recovery provides better psychological comfort in post-exercise recovery.